Acclimatization of a microbial consortium into a stable biofilm to produce energy and 1,3-propanediol from glycerol in a microbial fuel cell - Halfeld, Gisele Giovanna [UNESP]; Almeida, Erica Janaina Rodrigues de [UNESP]; Reginatto, Valeria; Andrade, Adalgisa Rodrigues de [UNESP] (Elsevier B.V., 2022)
Glycerol, a by-product of biodiesel production, is a potential substrate for producing electricity and value-added products in bioelectrochemical systems. Here, we demonstrate a strategy to establish a highly specific energy-producing biofilm from glycerol in a microbial fuel cell (MFC). The MFC fed with 1 g L-1 glycerol achieved maximum voltage, power density, and current of 0.4 V, 152 mW m-2, and 19.0 mA m-2, respectively, operating at a resistance of 1000 U. These values were much higher than the values previously described for the same glycerol concentration. High-throughput sequencing demonstrated that substituting acetate for glycerol diminished the anodic microbial diversity. In addition, glycerol shifted the microbial community composition from electroactive bacteria genera such as Delftia, Advenella, Thauera, Stenotrophomonas, and Dysgonomonas to bacteria with dual
Keywords: Glycerol; Power generation; Microbial fuel cell; Biofilm; 3-Propanediol